ANALISIS STRATEGI OPERASIONAL DAN PEMASARAN PADA UMKM KUE ULANG TAHUN ADOOREBAKES - gracella margaretha (Jurnal Pengabdian Masyarakat FKIP UTP, 2026)
This community service project aims to analyze the operational activities, marketing strategies, Customer Relationship Management (CRM), and business management of the Adoorebakes MSME, a birthday cake manufacturer. The methods employed included direct observation and data collection through interviews with the business owner. Based on the results of the community service project, Adoorebakes operates a make-to-order production process, focusing on the quality of ingredients and attractive cake designs tailored to customer demand. In terms of marketing, the business utilizes social media platforms as its primary promotional tool to expand its market reach. The implementation of Customer Relationship Management (CRM) is reflected through responsive communication, personalized services, and the ability to fulfill customer preferences according to requested designs and themes, which contributes to customer satisfaction and loyalty. In terms of operational management, Adoorebakes remains relatively simple but effectively meets customer demand. Challenges include managing production time, demand fluctuations, and resource constraints. Nevertheless, the business offers significant growth opportunities through improved marketing strategies, product innovation, CRM implementation, and more structured business management. The conclusions from this observation indicate that the Adoorebakes MSME has the potential to thrive in the competitive birthday cake industry, provided improvements in operational management and more effective business strategies are implemented.